Sequence-specific detection of different strains of LCMV in a single sample using tentacle probes - Franco, Lina S. (Virol J, 2017)
BACKGROUND: Virus infections often result in quasispecies of viral strains that can have dramatic impacts on disease outcomes. However, sequencing of viruses to determine strain composition is time consuming and often cost-prohibitive. Rapid, cost-effective methods are needed for accurate measurement of virus diversity to understand virus evolution and can be useful for experimental systems. METHODS: We have developed a novel molecular method for sequence-specific detection of RNA virus genetic variants called Tentacle Probes. The probes are modified molecular beacons that have dramatically improved false positive rates and specificity in routine qPCR. To validate this approach, we have designed Tentacle Probes for two different strains of Lymphocytic Choriomeningitis Virus (LCMV) that differ by only 3 nucleotide substitutions, the parental Armstrong and the more virulent Clone-13 strain. One of these mutations is a missense mutation in the receptor protein GP1 that leads to the Armstrong strain to cause an acute infection and Clone-13 to cause a chronic infection instead. The probes were designed using thermodynamic calculations for hybridization between target or non-target sequences and the probe. RESULTS: Using this approach, we were able to distinguish these two strains of LCMV individually by a single nucleotide mutation. The assay showed high reproducibility among different concentrations of viral cDNA, as well as high specificity and sensitivity, especially for the Clone-13 Tentacle Probe. Furthermore, in virus mixing experiments we were able to detect less than 10% of Clone-13 cDNA diluted in Armstrong cDNA. CONCLUSIONS: Thus, we have developed a fast, cost-effective approach for identifying Clone-13 strain in a mix of other LCMV strains. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12985-017-0863-9) contains supplementary material, which is available to authorized users.